Narrow-Margin Hepatectomy Resulted in Higher Recurrence and Lower Overall Survival for R0 Resection Hepatocellular Carcinoma - Liu, Lihong; Shui, Yongjie; Yu, Qianqian; Guo, Yinglu; Zhang, Lili; Zhou, Xiaofeng; Yu, Risheng; Lou, Jianying; Wei, Shumei; Wei, Qichun (Frontiers in Oncology, 2021)
Purpose: To evaluate the impact of resection margin on recurrence pattern and survival for hepatocellular carcinoma (HCC) with narrow margin resection, with the aim to guide postoperative treatment. Materials and methods: 240 HCC patients after curative hepatectomy between 2014 and 2016 were reviewed retrospectively. The cases were divided into narrow-margin (width of resection margin <1cm, n=106) and wide-margin (width of resection margin ≥1cm, n=134) groups based on the width of resection margin. Recurrence pattern, recurrence-free survival (RFS) and overall survival (OS) were compared between the above two groups. An additional cohort of 9 cases with positive margin plus post-operative sterotactic body radiotherapy (SBRT) was also analyzed for the recurrence pattern. Results: Postoperative recurrence was found in 128 (53.3%) patients. The recurrence rate was significantly higher in narrow-margin group than that in wide-margin group (P=0.001), especially for the pattern of marginal recurrence (20.8% vs 4.5%, P=0.003). The 1-, 2-, 3-year RFS rates for the narrow-margin and wide-margin groups were 55.8%, 43.9%, 36.9%, and 78.7%, 67.9%, 60.2%, respectively, with significant difference between the two groups (P<0.001). Patients with narrow margin showed a tendency of decreased OS than those with wide margin (P<0.001). As comparison, the 9 cases with positive margin treated with postoperative SBRT showed low recurrence rate and no marginal recurrence was found. Conclusion: Patients with narrow resection margin were associated with higher recurrence rate and worse survival than those with wide resection margin. These patients may benefit from adjuvant local treatment, such as radiotherapy.